Pegmatitic beryl as indicator of melt evolution: example from the Velasco district, Pampeana Pegmatite Province, Argentina, and review of worldwide occurrences - Sardi, Fernando Guillermo (2014)
Rare-element class, beryl type, beryl-columbite-phosphate subtype pegmatites of the Velasco district from the Pampeana Pegmatite Province, Argentina, contain varieties of green, yellow, and aquamarine beryl. The major and trace element chemistry and dimensions of the unit cell parameters of beryl from ten pegmatites from the Velasco district were used to identify differences among beryl types, determine chromophore elements, and determine the relative degree of fractionation of the pegmatites. Concentrations of Rb, Li, Cs, and Na in all beryls analyzed are among the lowest measured in pegmatitic beryl of similar colors worldwide. Within and among individual pegmatites, an increase in Li and Cs contents and decrease in Na/Li ratios in the order green beryl → yellow beryl → aquamarine suggest that green beryl formed in the early stages of crystallization of the pegmatites while yellow beryl and aquamarine formed from more evolved fluids in the late stages of crystallization. The chemical variations from green beryl to yellow beryl to aquamarine reflect crystallization during melt fractionation and/or crystallization of Fe-Mn phosphate minerals. Beryl from the El Bolsoncito and El Principio pegmatites, with the highest Li and Cs and some of the lowest Fe + Mg contents in the studied beryl, reflects the highest degree of evolution among the Velasco pegmatites. Within individual pegmatites Cr contents in beryl decrease in the order green beryl → yellow beryl, and green beryl → aquamarine, consistent with Cr being a chromophore element for green beryl. Niobium contents increase from green to yellow beryl, and from green beryl to aquamarine, indicating that Nb tends to concentrate in late forms of beryl. The absence of a systematic change in the size of unit cell parameters a and c with varying compositions and the small size of the c parameter reflect the extremely limited incorporation of Li, Na, and Cs in the mineral. A compilation of beryl compositions worldwide shows the highest degree of fractionation for the Tanco, Koktokay No. 3, Minas Gerais, Kaatiala, Namivo, Bikita, Czech Republic, and Greer Lake pegmatites.